Social innovation in high-quality agricultural systems: metrics for assessing processes and outcomes - Santini Pigatto, Giuliana Aparecida; Brunori, Gianluca (Innovation: The European Journal of Social Science Research, 2021)
Social innovation and high-quality agricultural systems are important for rural development. However, there is little information on methods for measuring the process and outcome of social innovation, particularly at the regional level. This study aimed to answer the research question: Which social innovation metrics can be applied to analyze rural development at the regional level? We carried out a systematic review of the literature on factors and indicators of social innovation, assessed the characteristics of social innovation in value-added agricultural production systems in developed countries, and proposed social innovation indicators for evaluating value-added agricultural systems in developing countries. Key elements of the process and outcome dimensions of social innovation were identified and used to generate factors, subfactors, indicators, and subindicators. The literature review showed that more research is needed on the outcomes of social innovation. Future studies should investigate the social transformations promoted by rural tourism and biodiversity valorization.
Number: 2
Keywords: Agriculture; Développement rural; Europe; Innovation sociale; Mesure d'impact; Réservé UdeM; Transformations sociales

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
Number: 3 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376
Keywords: Innovation ouverte; Laboratoire vivant; Living Labs; Mesure d'impact; Réservé UdeM

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

Théorie du changement - Esplanade Québec (Esplanade, 2021)
Découvrez et téléchargez l'impact gaps canvas qui aidera les entrepreneurs d'impact à comprendre et valider votre impact. Une théorie du changement est un outil qui vous aide à décrire les changements que vous voulez voir se produire et la manière dont vous comptez y parvenir. Plus spécifiquement, elle vous aide à décrire le problème que vous essayez de résoudre, les changements que vous voulez opérer (vos résultats) et ce que vous allez mettre en place pour pouvoir y arriver (activités). Elle est une représentation dynamique et une illustration du comment et du pourquoi il est envisagé que le changement désiré s’opère dans un contexte particulier.
Keywords: Canevas; Libre accès; Mesure d'impact; Montréal; Optimisation; Outils; Planification; Québec; Théorie du changement

The Impact of Societal and Social Innovation: a Case-Based Approach - Lin, Carol Yeh-Yun; Chen, Jeffrey (Springer Singapore, 2016)
Keywords: Mesure d'impact; Réservé UdeM

La transition numérique des structures œuvrant au service de l’intérêt général peut-elle augmenter leur impact social ? - Sibieude, Thierry; Leclerc, Élise (Question(s) de management, 2021)
Quelles sont les conditions de la maximisation de l’impact, et notamment sa pérennisation, du mécénat de compétence tech au profit des organisations dont la mission relève directement et prioritairement de la gestion du bien commun au service de l’intérêt général ? Telle est la question de recherche que la Fondation Devoteam a posée à l’ESSEC au moment de la mise en place de son programme #TechFor-People, afin de s’assurer de la pertinence de ce programme pour répondre aux besoins sur le long terme des structures de l’ESS (Économie Sociale et Solidaire) en transformation digitale. Afin de répondre à cette problématique l’ESSEC a réalisé une évaluation d’impact social fondée sur les cadres théoriques de la théorie du changement et de la théorie des parties prenantes, avec l’analyse de besoin, une collecte de données qualitatives ex-ante ainsi qu’une collecte de données quantitative ex-ante et ex-post. L’analyse de ces collectes révèle une dichotomie spécifique aux structures de l’ESS utilisant le programme que nous avons catégorisées en Tech Driven d’une part, ou Tech Powered d’autre part, avec des besoins et des conditions de pérennisation spécifiques en fonction de la catégorie qui leur correspond.
Number: 5 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: EMS Editions
Keywords: Mesure d'impact; Réservé UdeM

How to measure the impact of social innovation initiatives? - Cunha, Jorge; Benneworth, Paul (International Review on Public and Nonprofit Marketing, 2020)
Academic literature about the idea of social innovation grew sharply over the last decade, with researchers trying to define its concept and presenting several examples of successful social innovations. However, to support the development of social innovation initiatives is important to have a conceptual framework that allows evaluating its true impact. The purpose of this paper is to identify the boundary conditions for an effective set of social innovation indicators, which will help to have a more informed decision-making process. The main conclusion is that the impact of social innovations can be conceived as a set of results that manifests itself through different time periods, at different spatial scales, and must take into account the value experienced by all stakeholders involved. Thus, since a positive social innovation outcome depends on diverse factors and conditions, being most often context-dependent, it means that rather than imposing a specific set of indicators, based on a ‘one-size-fits-all’ approach a measuring process procedure should be adopted to assess the impact of social innovations.
Number: 1 Avons la version pre-print
Keywords: Mesure d'impact; Version libre-accès Open Repository

Measuring Innovation Everywhere: The Challenge of Better Policy, Learning, Evaluation and Monitoring - Gault, Fred (Cheltenham, UK:Elgar, 2020)
Discusses the measurement of innovation and the use of the resulting indicators to shape policy, exploring whether innovation can be measured everywhere, not just in the business sector, in a rapidly changing world. Reviews systems, innovation, and innovation policy. Details current innovation policies. Describes scoreboards and their use for monitoring existing innovation policy. Focuses on the implementation of innovation policy. Presents the general definition of innovation applicable in all economic sectors and considers the importance of language in the innovation discourse. Provides the conceptual framework for the specification of the statistical measurement of innovation. Addresses non-sector-specific innovation in the informal economy, green economy, social innovation, and innovation resulting from the use of general-purpose technologies. Examines global challenges for innovation such as sustainability restrictions. Considers the future of innovation in the digital economy, informal economy, and social innovation. Gault is Professorial Fellow at UNU-MERIT, Professor Extraordinary at Tshwane University of Technology, and Visiting Professor at the University of Johannesburg. Index.
Pages: xvii, 128
Keywords: Mesure d'impact; Réservé UdeM

Measurement System for the Analysis of Social Innovation in Projects - Martez, Nuvia; Dieste, Eugenia (2019 7th International Engineering, Sciences and Technology Conference (IESTEC), 2019)
Recent studies regarding Social Innovation (SI) represent a small percentage of the academic research, and as a consequence the methodologies, focuses, and practices about this topic have not been consolidated. The social innovations generate intangible benefits, mainly qualitative, which makes it difficult to evaluate, even though few authors have indicated the distinguishable characteristics of SI there is not consensus about how to measure it. This document presents the results of a research project with the main objective of identifying the criteria distinguishing SI, and to propose a tool to facilitate its measurement, tracing, and potential assessment. A systematic criteria revision was performed along with a comparative study of eight SI projects from Latin America, prioritizing such criteria. With this information a proposal was developed, including the criteria, associated questions and ponderations. In order to validate the utility of this tool, the evaluation of the project "Implementation of a Solar-Eolic hybrid system in a school in remoted and insolated areas" was performed. The evaluation process allowed to inquire and discover the weaknesses and to explore the limiting causes for every criterion, giving place for recommendations directed to the developers and beneficiaries of the project. Throughout this tool it can be determined whether a project can be considered a successful SI or not; in case of not being successful, the method exerts a simple view of the characteristics that need improvement.
Keywords: Amérique latine; Mesure d'impact; Réservé UdeM

Mesurer l’impact de l’innovation sociale : quelles perspectives en dehors de la théorie du changement ? - Besançon, Emmanuelle; Chochoy, Nicolas (RECMA, 2019)
La mesure de l’impact social est devenue un sujet majeur dans le débat relatif au financement de l’innovation sociale. Plusieurs rapports de référence ont été publiés dans ce sens. Ces travaux récents, en s’inscrivant tous dans le cadre logique de la gestion axée sur les résultats (GAR), également appelée « théorie du changement », renouvellent la construction d’une relation problématique : le lien causal et la mesure de sa preuve. À partir d’une approche institutionnaliste de l’innovation sociale, cet article expose les impasses de la GAR dans l’évaluation des innovations sociales et souligne que d’autres voies sont possibles. Les auteurs proposent ainsi de placer l’aspiration sociale au cœur du processus d’évaluation.
Number: 2 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association RECMA
Keywords: Gestion axée sur les résultats; Mesure d'impact; Réservé UdeM

Know Your Impact (and in Praise of Better Borrowing) - Mulgan Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
This chapter is about evidence and whether we can, or should, know our impact, the effect we have in the world. It addresses the difficulties as well as the possibilities of evidence for innovators and politicians, civil servants and head teachers, charities and doctors. I also touch on the question at the level of daily life, the moral question of whether we help those around us to be healthier, happier and more prosperous. Knowing our own impacts is, I argue, as much a moral prerogative as the traditional philosophical injunction of knowing ourselves.The enlightenment storyMany of us imbibed from an early age what can be called the enlightenment story. In this story new knowledge is steadily accumulated, mainly in universities and from academic journals. Theories are invented, tested, refuted and then improved. Scepticism helps to refine them and, as Wittgenstein wrote, the child first learns belief and only then learns doubt. You could say that at school we learn knowledge, and then at university we learn to question that knowledge.Belief is strengthened precisely because it has already been knocked down. And so, accumulating knowledge shows that this medicine, that economic policy or this teaching method works and many others don’t. The successful method then spreads, because when you design a better mousetrap the world beats a path to your door. It spreads because people are rational and want to do better and are persuaded by evidence. And so, the world progresses. Light replaces darkness. Effective solutions displace failed ones.It's easy to mock the enlightenment story. The sociologists of science have shown a much messier pattern of change – full of barriers, wilful resistance and peer pressure. But the old enlightenment story contains a good deal of truth and is preferable to the alternatives. Because of intense pressures to act on evidence, and habits of doubt among maintenance staff and engineers, aircraft do not drop out of the sky. Smoking made the slow progress from evidence of harm, through taxes and warnings to full-scale bans, and millions of lives were saved.Experimental methods have been used for many decades.
Keywords: Mesure d'impact; Réservé UdeM

The Evolution of Measures That Matter: How Do We Know If Social Innovation is Working? - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In the kingdom of ends everything has either a price or a dignity. What has a price can be replaced by something else as its equivalent; what on the other hand is raised above all price and therefore admits of no equivalent has a dignity.One of the fascinating features of the history of science is how often new ways of seeing preceded new insights. The achromatic-lens microscope in the early 19th century paved the way for germ theory, and X-ray crystallography in the early 20th century played a vital role in the later discovery of the structure of DNA. In the same way flows of data – for example, about how people move around a city, or how blood cells change – can prompt new insights.But how important is measurement to social change? Many people are attracted to metrics and indices of all kinds. But, as my colleague Mark Moore used to warn, ‘do you really think the leaders of the Civil Rights Movement were counting the placards or measuring the decibels of their cries for human rights?’ In social change, as in our own daily lives, measurement often feels inappropriate for the things that matter most.This chapter examines some of the history of social observation as a tool for public policy, social innovation and social change, and I suggest where it might lead in the future. Without some means of measurement, it can be hard to know if a social innovation is good. It may feel good to the beneficiaries – but still be less effective than an alternative. Or it may work well for one group but not another. And, even if it may not be appropriate to measure the passions of movements, once these ideas become part of the mainstream, and are transformed into the cool logic of laws, regulations and programmes, measurements do start to matter a lot, as the Civil Rights Movement discovered.A short history of measurementFor centuries, governments have sought to map and measure social phenomena in order to better exercise control over them. In the modern era these attempts can be traced back to figures like Sir William Petty in England and the cameralists in Prussia.
Keywords: Mesure d'impact; Réservé UdeM

Mature Social Economy Enterprise and Social Innovation: The Case of the Desjardins Environmental Fund - Vézina, Martine; Malo, Marie-Claire; Ben Selma, Majdi (Annals of Public and Cooperative Economics, 2017)
This study seeks to understand the nature and process of social innovation driven by mature social economy enterprises, and the innovative capability that supports it. The research examines enterprise capabilities by means of the institutional approach to social innovation and the Resource-Based View theory (RBV). Based on grounded theory, this research focuses on a single case, the creation of the Desjardins Environment Fund (DEF). Launched 25 years ago,1 DEF is the first mutual fund in North America to include extra-financial criteria in its evaluation of business environmental management practices (fund securities) for the information of individual investors. The findings of this empirical research show how a major cooperative bank can generate social innovation and how this entails organizational innovations. The findings also reveal how these innovations benefit from the strategic and process resources that the Desjardins Movement managed to develop while taking into account both its core business (as a bank) and its purpose (as a cooperative). This study shows that the innovative potential of the mature social economy enterprise should not be underestimated.
Number: 2 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/apce.12169
Keywords: Canada; Mesure d'impact; Resource-Based View theory (RBV); Réservé UdeM

Is measuring social innovation a mission impossible? - Mihci, Hakan (Innovation, 2020)
The main aim of the paper is to question the viability of measuring social innovation with the current state of knowledge on the one hand, and to make suggestions for better measurement of it on the other. To reach this aim, the literature on the traditional measures of technological innovation and the previous attempts of measuring social innovation is surveyed. Despite relatively narrow scope of the literature mainly originated from the very recent and pioneer experiments, one may argue that the first findings do not present a promising picture for future studies. Therefore, existing trials to measure social innovation have to be critically screened to ascertain problematic areas, and hence, to provide plausible solutions. The problems with social innovation metrics are not only limited with obtaining concrete and trustworthy results, but also extended to statistical, methodological and even conceptual spheres.
Number: 3
Keywords: Mesure d'impact; Réservé UdeM

Our impact - Schwab Foundation for Social Entrepreneurship (Schwab Foundation for Social Entrepreneurship, 2021)
The Schwab Foundation for Social Entrepreneurship launched its 2020 Impact Report which showcases the collective impact of the Schwab Foundation social entrepreneur community.
Keywords: Europe; Mesure d'impact; OBNL

Exemple - Rapport d'impact 2020-2021 - MILA (Mila, 2021)
Keywords: Intelligence artificielle; International; Libre accès; Mesure d'impact; Québec

Dévoilement d’un espace web sur l’évaluation et la mesure d’impact en économie sociale - TIESS (Territoires innovants en Économie sociale et solidaire liaison et transfert, 2022)
Qu’est-ce que la mesure d’impact social ? Comment mesurer son impact social ? Pourquoi l’évaluer ? Pour qui ? Quelle approche utiliser ? Qui est actif dans le domaine ? Quelles sont les méthodes ? Quels sont les indicateurs ? Que peut-on dire sur l’impact de l’économie sociale au Québec à ce jour ? Ces questions vous interpellent ? Le TIESS dévoile aujourd’hui un
Keywords: Innovation sociale; Intelligence collective; Libre accès; Mesure d'impact; Outils; Québec; Économie sociale; Économie solidaire

Théorie du changement - Esplanade Québec (Esplanade, 2021)
Une théorie du changement est un outil qui vous aide à décrire les changements que vous voulez voir se produire et la manière dont vous comptez y parvenir. Plus spécifiquement, elle vous aide à décrire le problème que vous essayez de résoudre, les changements que vous voulez opérer (vos résultats) et ce que vous allez mettre en place pour pouvoir y arriver (activités). Elle est une représentation dynamique et une illustration du comment et du pourquoi il est envisagé que le changement désiré s’opère dans un contexte particulier.
Keywords: Canevas; Libre accès; Mesure d'impact; Montréal; Optimisation; Outils; Planification; Québec; Théorie du changement

Exemple - Rapport d'impact 2020-2021 - MILA (Mila, 2021)
Keywords: Intelligence artificielle; International; Libre accès; Mesure d'impact; Québec

Dévoilement d’un espace web sur l’évaluation et la mesure d’impact en économie sociale - TIESS (Territoires innovants en Économie sociale et solidaire liaison et transfert)
Qu’est-ce que la mesure d’impact social ? Comment mesurer son impact social ? Pourquoi l’évaluer ? Pour qui ? Quelle approche utiliser ? Qui est actif dans le domaine ? Quelles sont les méthodes ? Quels sont les indicateurs ? Que peut-on dire sur l’impact de l’économie sociale au Québec à ce jour ? Ces questions vous interpellent ? Le TIESS dévoile aujourd’hui un
Keywords: Innovation sociale; Intelligence collective; Libre accès; Mesure d'impact; Outils; Québec; Économie sociale; Économie solidaire

L'impact des événements d'innovation ouverte - Armellini, Fabiano; Veilleux, Sophie (2021)
L’objectif de ce rapport (rédigé notamment par Fabiano Armellini et Sophie Veilleux) est de présenter les meilleures pratiques, les indicateurs de succès ainsi que les mesures d’impact des événements d’innovation ouverte sur leurs écosystèmes respectifs. Ainsi, chaque acteur est en mesure d’optimiser sa participation afin d’en retirer un maximum de bénéfices et d’en faire profiter son écosystème. Ce rapport offre aussi plusieurs recommandations.
N'est plus disponible sur le site PB 2021-12-07
Keywords: Innovation ouverte; Meilleures pratiques; Mesure d'impact

Social innovation in high-quality agricultural systems: metrics for assessing processes and outcomes - Santini Pigatto, Giuliana Aparecida; Brunori, Gianluca (Innovation: The European Journal of Social Science Research, 2021)
Social innovation and high-quality agricultural systems are important for rural development. However, there is little information on methods for measuring the process and outcome of social innovation, particularly at the regional level. This study aimed to answer the research question: Which social innovation metrics can be applied to analyze rural development at the regional level? We carried out a systematic review of the literature on factors and indicators of social innovation, assessed the characteristics of social innovation in value-added agricultural production systems in developed countries, and proposed social innovation indicators for evaluating value-added agricultural systems in developing countries. Key elements of the process and outcome dimensions of social innovation were identified and used to generate factors, subfactors, indicators, and subindicators. The literature review showed that more research is needed on the outcomes of social innovation. Future studies should investigate the social transformations promoted by rural tourism and biodiversity valorization.
Keywords: Agriculture; Développement rural; Europe; Innovation sociale; Mesure d'impact; Réservé UdeM; Transformations sociales

La transition numérique des structures œuvrant au service de l’intérêt général peut-elle augmenter leur impact social ? - Sibieude, Thierry; Leclerc, Élise (Question(s) de management, 2021)
Quelles sont les conditions de la maximisation de l’impact, et notamment sa pérennisation, du mécénat de compétence tech au profit des organisations dont la mission relève directement et prioritairement de la gestion du bien commun au service de l’intérêt général ? Telle est la question de recherche que la Fondation Devoteam a posée à l’ESSEC au moment de la mise en place de son programme #TechFor-People, afin de s’assurer de la pertinence de ce programme pour répondre aux besoins sur le long terme des structures de l’ESS (Économie Sociale et Solidaire) en transformation digitale. Afin de répondre à cette problématique l’ESSEC a réalisé une évaluation d’impact social fondée sur les cadres théoriques de la théorie du changement et de la théorie des parties prenantes, avec l’analyse de besoin, une collecte de données qualitatives ex-ante ainsi qu’une collecte de données quantitative ex-ante et ex-post. L’analyse de ces collectes révèle une dichotomie spécifique aux structures de l’ESS utilisant le programme que nous avons catégorisées en Tech Driven d’une part, ou Tech Powered d’autre part, avec des besoins et des conditions de pérennisation spécifiques en fonction de la catégorie qui leur correspond.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: EMS Editions
Keywords: Mesure d'impact; Parties prenantes; Réservé UdeM; Théorie du changement

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Num Pages: 1 Place: New York, United Kingdom Publisher: Elsevier Science Ltd.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

How to measure the impact of social innovation initiatives? - Cunha, Jorge; Benneworth, Paul (International Review on Public and Nonprofit Marketing, 2020)
Academic literature about the idea of social innovation grew sharply over the last decade, with researchers trying to define its concept and presenting several examples of successful social innovations. However, to support the development of social innovation initiatives is important to have a conceptual framework that allows evaluating its true impact. The purpose of this paper is to identify the boundary conditions for an effective set of social innovation indicators, which will help to have a more informed decision-making process. The main conclusion is that the impact of social innovations can be conceived as a set of results that manifests itself through different time periods, at different spatial scales, and must take into account the value experienced by all stakeholders involved. Thus, since a positive social innovation outcome depends on diverse factors and conditions, being most often context-dependent, it means that rather than imposing a specific set of indicators, based on a ‘one-size-fits-all’ approach a measuring process procedure should be adopted to assess the impact of social innovations.
Avons la version pre-print
Keywords: Mesure d'impact; Université; Version libre-accès Open Repository

Measuring Innovation Everywhere: The Challenge of Better Policy, Learning, Evaluation and Monitoring - Gault, Fred (Cheltenham, UK:Elgar, 2020)
Discusses the measurement of innovation and the use of the resulting indicators to shape policy, exploring whether innovation can be measured everywhere, not just in the business sector, in a rapidly changing world. Reviews systems, innovation, and innovation policy. Details current innovation policies. Describes scoreboards and their use for monitoring existing innovation policy. Focuses on the implementation of innovation policy. Presents the general definition of innovation applicable in all economic sectors and considers the importance of language in the innovation discourse. Provides the conceptual framework for the specification of the statistical measurement of innovation. Addresses non-sector-specific innovation in the informal economy, green economy, social innovation, and innovation resulting from the use of general-purpose technologies. Examines global challenges for innovation such as sustainability restrictions. Considers the future of innovation in the digital economy, informal economy, and social innovation. Gault is Professorial Fellow at UNU-MERIT, Professor Extraordinary at Tshwane University of Technology, and Visiting Professor at the University of Johannesburg. Index.
Chapitre 8.5 (p.73-79) Innovation sociale
Keywords: Mesure d'impact; Réservé UdeM

Is measuring social innovation a mission impossible? - Mihci, Hakan (Innovation, 2020)
The main aim of the paper is to question the viability of measuring social innovation with the current state of knowledge on the one hand, and to make suggestions for better measurement of it on the other. To reach this aim, the literature on the traditional measures of technological innovation and the previous attempts of measuring social innovation is surveyed. Despite relatively narrow scope of the literature mainly originated from the very recent and pioneer experiments, one may argue that the first findings do not present a promising picture for future studies. Therefore, existing trials to measure social innovation have to be critically screened to ascertain problematic areas, and hence, to provide plausible solutions. The problems with social innovation metrics are not only limited with obtaining concrete and trustworthy results, but also extended to statistical, methodological and even conceptual spheres.
Keywords: Indicateur; Innovation; Innovation sociale; Innovation technologique; Mesure d'impact; Réservé UdeM

Mesurer l’impact de l’innovation sociale : quelles perspectives en dehors de la théorie du changement ? - Besançon, Emmanuelle; Chochoy, Nicolas (RECMA, 2019)
La mesure de l’impact social est devenue un sujet majeur dans le débat relatif au financement de l’innovation sociale. Plusieurs rapports de référence ont été publiés dans ce sens. Ces travaux récents, en s’inscrivant tous dans le cadre logique de la gestion axée sur les résultats (GAR), également appelée « théorie du changement », renouvellent la construction d’une relation problématique : le lien causal et la mesure de sa preuve. À partir d’une approche institutionnaliste de l’innovation sociale, cet article expose les impasses de la GAR dans l’évaluation des innovations sociales et souligne que d’autres voies sont possibles. Les auteurs proposent ainsi de placer l’aspiration sociale au cœur du processus d’évaluation.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association RECMA
Keywords: Gestion axée sur les résultats; Mesure d'impact; Réservé UdeM

Measurement System for the Analysis of Social Innovation in Projects - Martez, Nuvia; Dieste, Eugenia (2019 7th International Engineering, Sciences and Technology Conference (IESTEC), 2019)
Recent studies regarding Social Innovation (SI) represent a small percentage of the academic research, and as a consequence the methodologies, focuses, and practices about this topic have not been consolidated. The social innovations generate intangible benefits, mainly qualitative, which makes it difficult to evaluate, even though few authors have indicated the distinguishable characteristics of SI there is not consensus about how to measure it. This document presents the results of a research project with the main objective of identifying the criteria distinguishing SI, and to propose a tool to facilitate its measurement, tracing, and potential assessment. A systematic criteria revision was performed along with a comparative study of eight SI projects from Latin America, prioritizing such criteria. With this information a proposal was developed, including the criteria, associated questions and ponderations. In order to validate the utility of this tool, the evaluation of the project "Implementation of a Solar-Eolic hybrid system in a school in remoted and insolated areas" was performed. The evaluation process allowed to inquire and discover the weaknesses and to explore the limiting causes for every criterion, giving place for recommendations directed to the developers and beneficiaries of the project. Throughout this tool it can be determined whether a project can be considered a successful SI or not; in case of not being successful, the method exerts a simple view of the characteristics that need improvement.
Keywords: Amérique latine; Mesure d'impact; Réservé UdeM

Know Your Impact (and in Praise of Better Borrowing) - Mulgan Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
This chapter is about evidence and whether we can, or should, know our impact, the effect we have in the world. It addresses the difficulties as well as the possibilities of evidence for innovators and politicians, civil servants and head teachers, charities and doctors. I also touch on the question at the level of daily life, the moral question of whether we help those around us to be healthier, happier and more prosperous. Knowing our own impacts is, I argue, as much a moral prerogative as the traditional philosophical injunction of knowing ourselves.The enlightenment storyMany of us imbibed from an early age what can be called the enlightenment story. In this story new knowledge is steadily accumulated, mainly in universities and from academic journals. Theories are invented, tested, refuted and then improved. Scepticism helps to refine them and, as Wittgenstein wrote, the child first learns belief and only then learns doubt. You could say that at school we learn knowledge, and then at university we learn to question that knowledge.Belief is strengthened precisely because it has already been knocked down. And so, accumulating knowledge shows that this medicine, that economic policy or this teaching method works and many others don’t. The successful method then spreads, because when you design a better mousetrap the world beats a path to your door. It spreads because people are rational and want to do better and are persuaded by evidence. And so, the world progresses. Light replaces darkness. Effective solutions displace failed ones.It's easy to mock the enlightenment story. The sociologists of science have shown a much messier pattern of change – full of barriers, wilful resistance and peer pressure. But the old enlightenment story contains a good deal of truth and is preferable to the alternatives. Because of intense pressures to act on evidence, and habits of doubt among maintenance staff and engineers, aircraft do not drop out of the sky. Smoking made the slow progress from evidence of harm, through taxes and warnings to full-scale bans, and millions of lives were saved.Experimental methods have been used for many decades.
Keywords: Mesure d'impact; Réservé UdeM

The Evolution of Measures That Matter: How Do We Know If Social Innovation is Working? - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In the kingdom of ends everything has either a price or a dignity. What has a price can be replaced by something else as its equivalent; what on the other hand is raised above all price and therefore admits of no equivalent has a dignity.One of the fascinating features of the history of science is how often new ways of seeing preceded new insights. The achromatic-lens microscope in the early 19th century paved the way for germ theory, and X-ray crystallography in the early 20th century played a vital role in the later discovery of the structure of DNA. In the same way flows of data – for example, about how people move around a city, or how blood cells change – can prompt new insights.But how important is measurement to social change? Many people are attracted to metrics and indices of all kinds. But, as my colleague Mark Moore used to warn, ‘do you really think the leaders of the Civil Rights Movement were counting the placards or measuring the decibels of their cries for human rights?’ In social change, as in our own daily lives, measurement often feels inappropriate for the things that matter most.This chapter examines some of the history of social observation as a tool for public policy, social innovation and social change, and I suggest where it might lead in the future. Without some means of measurement, it can be hard to know if a social innovation is good. It may feel good to the beneficiaries – but still be less effective than an alternative. Or it may work well for one group but not another. And, even if it may not be appropriate to measure the passions of movements, once these ideas become part of the mainstream, and are transformed into the cool logic of laws, regulations and programmes, measurements do start to matter a lot, as the Civil Rights Movement discovered.A short history of measurementFor centuries, governments have sought to map and measure social phenomena in order to better exercise control over them. In the modern era these attempts can be traced back to figures like Sir William Petty in England and the cameralists in Prussia.
Keywords: Mesure d'impact; Réservé UdeM

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376
Keywords: Innovation ouverte; Laboratoire vivant; Living Labs; Mesure d'impact; Réservé UdeM

Mature Social Economy Enterprise and Social Innovation: The Case of the Desjardins Environmental Fund - Vézina, Martine; Malo, Marie-Claire; Ben Selma, Majdi (Annals of Public and Cooperative Economics, 2017)
This study seeks to understand the nature and process of social innovation driven by mature social economy enterprises, and the innovative capability that supports it. The research examines enterprise capabilities by means of the institutional approach to social innovation and the Resource-Based View theory (RBV). Based on grounded theory, this research focuses on a single case, the creation of the Desjardins Environment Fund (DEF). Launched 25 years ago,1 DEF is the first mutual fund in North America to include extra-financial criteria in its evaluation of business environmental management practices (fund securities) for the information of individual investors. The findings of this empirical research show how a major cooperative bank can generate social innovation and how this entails organizational innovations. The findings also reveal how these innovations benefit from the strategic and process resources that the Desjardins Movement managed to develop while taking into account both its core business (as a bank) and its purpose (as a cooperative). This study shows that the innovative potential of the mature social economy enterprise should not be underestimated.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/apce.12169
Keywords: Canada; Mesure d'impact; Resource-Based View theory (RBV); Réservé UdeM

The Impact of Societal and Social Innovation: a Case-Based Approach - Lin, Carol Yeh-Yun; Chen, Jeffrey (Springer Singapore, 2016)
Keywords: Asie; Changement systémique; Entrepreneuriat social; Europe; Innovation; Innovation sociale; Innovation sociétale; Mesure d'impact; Parties prenantes; Processus d'innovation; Réservé UdeM; Étude de cas

Our impact - Schwab Foundation for Social Entrepreneurship (Schwab Foundation for Social Entrepreneurship)
The Schwab Foundation for Social Entrepreneurship launched its 2020 Impact Report which showcases the collective impact of the Schwab Foundation social entrepreneur community.
Keywords: Europe; Mesure d'impact; OBNL